Vaping, smoking and risk of early onset lung cancer - Bittoni, Marisa A.; Carbone, David P.; Harris, Randall E. (Frontiers in Oncology, 2026)
Lung cancer is the leading cause of cancer mortality worldwide, including young adults. While it is well known that cigarette smoking is the dominant risk factor for lung cancer, the inhalation of heated aerosolized vaping oil has now replaced cigarette smoking as the major source of nicotine among young people. We, therefore, studied the potential role of both vaping and cigarette smoking in the development of early onset lung cancer. Using a case-control study design, we compared the smoking and vaping habits of 256 young adults (< 50 years of age) diagnosed with pathologically confirmed lung cancer to that of 2,921 control subjects without cancer that were group matched by age (within 5 years), sex, race and location to the cases. The odds ratio for those who both vaped and smoked (OR = 13.8, 95% CI: 7.7-24,9) was 2.8 times higher than for smoking alone (OR = 5.0, 95% CI: 3.7-6.9). Pulmonary adenocarcinomas accounted for 72% of the early onset lung tumors among the cases, and risk estimates for this specific cell type were 3.7 times higher for those who smoked and vaped (OR = 14.8, 95% CI = 8.0-27.4) compared to those who only smoked (OR = 4.0, 95% CI = 2.9-5.6). Our findings suggest that compared to smoking alone, vaping and smoking together accelerate lung cancer risk among young people, particularly in the development of pulmonary adenocarcinoma.